2010
DOI: 10.1152/ajplung.00309.2009
|View full text |Cite
|
Sign up to set email alerts
|

SOD and inhaled nitric oxide normalize phosphodiesterase 5 expression and activity in neonatal lambs with persistent pulmonary hypertension

Abstract: Phosphodiesterase 5 (PDE5) and soluble guanylate cyclase (sGC) are key regulators of cGMP and pulmonary vascular tone. We sought to determine the impact of mechanical ventilation with O(2) with or without inhaled nitric oxide (iNO) or recombinant human Cu/Zn SOD (rhSOD) on sGC, PDE5, and cGMP in the ovine ductal ligation model of persistent pulmonary hypertension of the newborn (PPHN). PPHN lambs were ventilated with 100% O(2) for 24 h alone or combined with either inhalation of 20 parts per million (ppm) iNO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 50 publications
3
86
2
Order By: Relevance
“…30 We previously reported that PDE5 activity is upregulated by increased ROS and that this effect is reversed by treatment with antioxidants in intact neonatal PPHN lambs and in smooth muscle cells isolated from them. 13,14,16 Therefore, we next investigated the effects of hyperoxia with and without hydrocortisone on oxidative stress in two subcellular compartments, using a previously characterized redox-sensitive probe, roGFP. As might be expected, exposure of PPHN FPASMC to hyperoxia for 24 hours resulted in increased oxidative stress, both in the cytosol and in the mitochondrial matrix (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 We previously reported that PDE5 activity is upregulated by increased ROS and that this effect is reversed by treatment with antioxidants in intact neonatal PPHN lambs and in smooth muscle cells isolated from them. 13,14,16 Therefore, we next investigated the effects of hyperoxia with and without hydrocortisone on oxidative stress in two subcellular compartments, using a previously characterized redox-sensitive probe, roGFP. As might be expected, exposure of PPHN FPASMC to hyperoxia for 24 hours resulted in increased oxidative stress, both in the cytosol and in the mitochondrial matrix (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…13 Moreover, PPHN may independently alter expression and activity of key enzymes in the NO-cGMP pathway. For example, ventilation with 100% oxygen increases PDE5 activity in PAs of PPHN lambs more than in control lambs, 13,14 and basal PDE5 activity is higher in FPASMC isolated from PPHN relative to healthy lambs. 16 Hyperoxia produces lung injury in part through increased formation of reactive oxygen species (ROS).…”
Section: Persistent Pulmonary Hypertension Of the Newborn (Pphn)mentioning
confidence: 92%
See 1 more Smart Citation
“…A dysfunctional EDNOsGC-cGMP-PKG signaling pathway constitutes one of the most fundamental and initial changes in the development of PH (1,33), resulting from aberrant expression of eNOS (34), reduced NO production caused by eNOS uncoupling (35)(36)(37)(38), diminished NO bioavailability caused by oxidative stress (39,40), diminished activities of sGC (41,42) and PKG (26,(43)(44)(45)(46), and augmented activity of phosphodiesterase type 5 (47).…”
Section: Edno As a Paracrine Regulatormentioning
confidence: 99%
“…Studies have demonstrated that recombinant human SOD (rhSOD) augments PDE-5 expression, vasodilatory response to iNO and oxygenation in PPHN lamb models [69,70]. Furthermore, rhSOD treatment appeared to block formation of oxidants like peroxynitrite and isoprostanes.…”
Section: Role Of Oxidant Stressmentioning
confidence: 99%